Decoration of silver nanoparticles on multi‐walled carbon nanotubes: Investigation of its anti‐acute leukemia property against acute myeloid leukemia and acute T cell leukemia. (9th January 2020) - Shahriari, Maryam; Hemmati, Saba; Zangeneh, Akram; Zangeneh, Mohammad Mahdi
Abstract : Recently, the development of carbon nanocomposites composed of carbon nanotubes and metal nanoparticles has attracted many interests because of their large potential for technological applications such as catalysts, sensors, biomedicine, and disinfection. In the present study, we described a simple chemistry method to synthesize multi‐walled carbon nanotubes (MWCNTs) decorated with silver nanoparticles (Ag‐NPs). Also, we investigated the antioxidant and anti‐acute leukemia activities against acute myeloid leukemia and acute T cell leukemia cell lines. Ag NPs‐MWCNTs were characterized and analyzed using common nanotechnology techniques including transmission electron microscopy (TEM), X‐ray diffraction (XRD), energy dispersive X‐ray spectroscopy (EDS), field emission‐scanning electron microscopy (FE‐SEM) and elemental mapping analysis. Also, 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) test was performed to assess the antioxidant capacities of AgNO3, MWCNTs, and Ag NPs‐MWCNTs. It revealed similar antioxidant potentials for Ag NPs‐MWCNTs and butylated hydroxytoluene. In MTT assay, Ag NPs‐MWCNTs had very low cell viability (very high anti‐acute leukemia properties) dose‐dependently against 32D‐FLT3‐ITD (Acute myeloid leukemia cell line), Human HL‐60/vcr (Acute myeloid leukemia cell line), Jurkat, Clone E6–1 (Acute T cell leukemia cell line), and J.RT3‐T3.5 (Acute T cell leukemia cell line) without any cytotoxicity on human umbilical vein endothelial cell line (HUVEC; Normal cell line). In conclusion, the synthesized Ag NPs‐MWCNTs revealed excellent antioxidant and cytotoxicity activities against acute myeloid leukemia and acute T cell leukemia cell lines in a dose depended manner. After confirming in the in vivo and clinical trials, these nanoparticles can be administrated in humans for the treatment of acute leukemia especially acute myeloid leukemia and acute T cell leukemia. Abstract : Formulation a chemotherapeutic dug in the field of hematology.